Knowledge Level of Mothers with Children Under Two Years Old About Stunting and the First 1000 Days of Life - Salsabilla, Tasya Salwa; Rahmatillah, Imat; Roza, Elvi (LPPM Universitas Jambi, 2025)
Background: Stunting is a condition of growth failure in children under five due to chronic malnutrition, particularly during the first 1,000 days of life. It is characterized by a shorter height compared to other children of the same age. The prevalence of stunting at Simpang Kawat Health Center in 2023 was recorded at 5.2%. However, low participation in child growth monitoring and maternal health programs indicates a lack of knowledge about stunting prevention. This study aims to quantitatively assess the knowledge level of mothers with children under two years old regarding stunting and the first 1,000 days of life. Method: This research used a quantitative cross-sectional study design. Data were collected using structured questionnaires distributed to 30 mothers at Simpang Kawat Health Center. The collected data were analyzed using descriptive statistical methods, including frequency distribution and percentage analysis, to assess respondents' knowledge levels. Result: The study revealed that 36.67% of respondents had a low level of knowledge about stunting, 46.67% had a moderate level, and only 16.66% demonstrated a good level of knowledge. The analysis showed that factors contributing to low knowledge levels included limited health education media, insufficient health worker resources, and low participation in posyandu and pregnancy classes. Conclusion: The findings indicate that the knowledge of mothers about stunting and the first 1,000 days of life is still inadequate. It is recommended that health centers implement more effective educational interventions, such as digital health campaigns, video-based learning, and interactive posyandu sessions, to enhance maternal awareness and participation in stunting prevention programs.